Illegal GMO Releases and Corporate Responsibility: Questioning the Effectiveness of Voluntary Measures - Jennifer Clapp (Ecological Economics, 2008)
Recent years have seen a number of cases of ‘accidental’ or ‘unintentional’ releases of genetically modified organisms (GMOs) that were not approved for human consumption or in some cases even for commercial planting. The environmental, economic, and social implications of the release of unapproved varieties of GMOs are potentially significant. The agricultural input industry has recently embraced Corporate Social Responsibility (CSR) reporting and some of its major players are participants in the UN's Global Compact. While CSR and the Global Compact encourage internalization of environmental costs and application of the precautionary principle amongst firms, in the case of illegal GMO releases these measures have proven extremely weak. In the case of illegal GMO releases, external, state-based regulation which places liability squarely on firms is likely to be much more successful as a means to prevent future occurrences of this problem.